Family Burden Related to Coping when Treating Hallucination Patients - Jek Amidos Pardede (Jurnal Ilmu Keperawatan Jiwa, 2020)
A person suffering from schizophrenia and having symptoms of hallucinations should get attention and care from the family. The family is the closest person to the patient and is considered to have an effect on the patient's recovery and is considered to be best aware of the patient's condition. So the family desperately needs patients in the care and treatment of patients. This study aims to identify the relationship of family burden with coping in treating hallucination patients. The design of this research is descriptive correlation using a cross sectional approach. The population in this study was the families of patients who came to bring their family members for outpatient 288 people. This sampling technique is accidental sampling of 24 respondents. The data collection tool uses a valid questionnaire that has been tested for validity and reability. Analyze the data using the Che square statistical test. The results showed that the majority of family expenses were subjective expenses of 62.5% and the majority of families were uns adaptive by 62.5% with a value of p = 0.022. In conclusion there is a significant relationship between the burden of family and coping when treating hallucination patients.